Enhanced bioscience content is urgently needed in UK pre-registration nursing curricula. (January 2019) - Perkins, C.
Abstract: Achieving adequate bioscience learning and assessment in pre registration nursing programs has been problematic for many decades. This has been discussed extensively in national and international health care literature. Despite this, the quantity and quality of bioscience content appears currently in many UK registered nursing programs, to be in a period of decline. Sub optimal bioscience knowledge of registered nurses has been consistently correlated with avoidable morbidity and mortality. An increasing evidence base indicates that a higher level of educated registered nurse, leads to improved health outcomes. It is therefore clear that continuing to fail to address the bioscience problem in nursing education has the potential to incur considerable adverse impact on the UK populations' health. The recent publication of new Nursing and Midwifery Council (NMC) standards of proficiency for registered nurses, and standards for pre-registration nursing programs require nurse education providers across the UK, to write new curriculum. The purpose of this discussion paper is to present the case for enhanced bioscience content within these. Highlights: Enhanced bioscience curriculum content is required to improve health outcomes. New proficiency and education standards give opportunity for the bioscience problem to be addressed. Inadequate bioscience knowledge causes avoidable health harm, and dissatisfaction in nurses. Increased bioscience knowledge is urgently required for the modern registered nursing role.